Use of selected types of crime analysis in modern criminological science: Experience of Ukraine and the world - Vasyl Topchii; Oksana Topchii; Maksym Zabarniy; Nataliіa Karpenko; Ihor Hrytsiuk (Wolters Kluwer Medknow Publications, 2023)
Background: In order to effectively prevent crime, the law enforcement agencies in Ukraine use criminological forecasting, through which it is possible to study and identify the main problems of crime. Aims and Objectives: The article aims to consider the modern criminological science in Ukraine and the world within the framework of criminological analysis used, determine the advantages and disadvantages of the selected types of criminological analysis, and substantiate the feasibility of investigating latent crimes. Materials and Methods: In the course of the study, the following general scientific and special research methods were used: formal-logical, system, statistical, and synthesis method. Results: The authors conclude by the conducted analytical study that such criminological analyses as regression, factorial, and monitoring are the most widespread at the present stage of criminological science development. These methods of criminological analysis were examined, their advantages and disadvantages were determined, and recommendations for their application in criminological science were given. It was established that the regression analysis is not found in many criminological studies, but the increase in crime rates both in Ukraine and in the world has led to the update in this direction. Conclusion: It has been proved that monitoring is the most frequent type of criminological analysis. This method is often used in criminological research to analyze statistical reporting publicly available to law enforcement agencies. The study has found it is advisable to investigate latent crime in addition to statistical indicators since it is several times higher than the level of officially registered criminal offenses in the country.